Metformin alleviates oxidative stress and enhances autophagy in diabetic kidney disease via AMPK/SIRT1-FoxO1 pathway - Ren, Huiwen; Shao, Ying; Wu, Can; Ma, Xiaoyu; Lv, Chuan; Wang, Qiuyue (Molecular and cellular endocrinology, 2020)
Metformin, as the basic pharmacological therapy and the first preventive drug in type 2 diabetes mellitus (T2DM), is proved to have potential protection in diabetic kidney disease (DKD). Here, we established a diabetic rat model induced by high-fat diet and low dose streptozotocin, and high glucose cultured rat mesangial cells (RMCs) pre-treated with metformin or transfected with AMPK, SIRT1 and FoxO1 small interfering RNA, and detected oxidative stress and autophagy related factors to explore the molecular mechanisms of metformin on DKD via adenosine monophosphate-activated protein kinase (AMPK)/silent mating type information regulation 2 homolog-1 (sirtuin-1, SIRT1)-Forkhead box protein O1 (FoxO1) pathway. We found that metformin effectively alleviated the disorders of glycolipid metabolism, renal function injury in diabetic rats, and relieved oxidative stress, enhanced autophagy and slowed down abnormal cell proliferation in high glucose cultured RMCs through AMPK/SIRT1-FoxO1 pathway, indicating the protective role of metformin against the pathological process of DKD. •Metformin can ease glucose and lipid metabolism disorders, renal dysfunction and proteinuria in diabetic rats.•Metformin can relieve the oxidative stress response and promote autophagy in high glucose cultured rat mesangial cells.•The protective effect of metformin on diabetic kidney disease may be achieved through the AMPK/SIRT1-FoxO1 pathway.